Analysis the geomorphological map and the slope map of the Shiwasor-Akhgler Valley Basin - Snur Ahmed Rasul; Ahmad Yassin Ali (Zanco Journal of Humanity Sciences)
This research focuses on studying and analyzing the forms and appearances of the earth in the study area, classifying them using satellites image and documenting them in the field through field study for the purpose of drawing a complete geomorphological map of the study area.